Leadership, Workload, and Culture: Impact on Organizational Performance through Service Quality - Marvel Marvel; Oscar Jayanagara (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2026)
Organizational performance in the healthcare sector is a multidimensional construct that includes financial outcomes, internal processes, learning and growth, and customer-related indicators. This study examines the effects of leadership style, workload, and organizational culture on hospital organizational performance, with service quality as a mediating variable. A quantitative cross-sectional design was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. Data were collected from nurses and patients at a leading private hospital in Tangerang, Indonesia, during November–December 2024. The analysis was conducted using valid responses from nurses and patients, supported by secondary data obtained from financial reports, press releases, and quarterly company presentations. The findings reveal that organizational culture has a significant positive effect on service quality and contributes to selected dimensions of organizational performance, particularly financial performance and learning and growth, through service quality mediation. In contrast, leadership style and workload do not show significant effects on service quality, indicating that hospital service quality may be more strongly shaped by shared organizational values, standardized procedures, and institutional culture than by individual leadership practices or perceived workload. Several performance dimensions, including internal process and customer-related outcomes, also show weak explanatory power, suggesting that these outcomes may be influenced by other factors beyond the proposed model, such as clinical interaction, patient expectations, operational efficiency, and external service conditions. This study contributes to organizational behavior and healthcare management literature by demonstrating the central role of organizational culture and service quality in strengthening hospital performance. The findings offer practical implications for hospital managers to develop a strong, structured, and service-oriented culture to improve healthcare delivery and organizational sustainability.